Cost-effectiveness of screenings for mental health in pregnancy: A systematic review - Kartikasari, Indah Dwi; Rahayu, Widya; Andriani, Novita; Pramesti, Sekar Ajeng; Safitri, Juliana; Icanervila, Ajeng Viska; Astuti, Andari Wuri (JHeS (Journal of Health Studies), 2024)
Mental disorders posses significant obstacles both during and after pregnancy for many women. Birth weight, premature birth, perinatal and infant deaths, postpartum psychopathology, emotional difficulties, inappropriate behavior in children and adolescents, and adverse effects on other people are just a few of the negative impacts that mental disorders are linked to during pregnancy in that family. Women with mental disorders may experience issues after giving birth, affecting their health throughout pregnancy. Infections, including depression, frequently go undiagnosed and receive subpar treatment despite routine interactions with medical providers during pregnancy. Hormonal changes impact Mother's body movements; for example, she moves more slowly and gets exhausted more rapidly. Pregnant ladies who are in this scenario tend to become indolent. A systematic assessment of research findings on the effectiveness of economic evaluation of mental health screening instruments during pregnancy is frequently used to encourage early detection of mental health in pregnant women as maternal reactions become more sensitive, irritable, and irritable. These investigations mostly used the EPDS and PHQ-9. For the systematic review portion of this investigation, the PRISM ScR 2020 Flowchart was employed, and the A search of the literature was done using the databases Pubmed and Whiley. This article was assessed using the CHEC-Extended checklist. Two reports satisfied the inclusion criteria after an investigation of 890 chosen papers. The systematic review identified three themes: cost, effectiveness, and threshold. Given the variety of treatments used to treat mental health issues in pregnant women, it is clear that using two approaches rather than just one will result in greater cost-effectiveness